Penggunaan Media Aplikasi Prezi Untuk Meningkatkan Hasil Belajar Seni Budaya Peserta Didik SMKN 2 Denpasar - I Wayan Sugama; Gusti Ayu Agung Trisna Prameswari; Dewa Ayu Dwita Respasti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Based on the initial observations indicating the low learning outcomes of students in the cultural arts learning, the implementation of Classroom Action Research (PTK) at SMK Negeri 2 Denpasar becomes a necessity. Therefore, this research will utilize the Prezi application as a media with the aim of improving the learning outcomes in cultural arts learning. This research is a type of Classroom Action Research consisting of two cycles, and each cycle comprises four stages. The subjects of this study are students of class X AK 1 at SMK Negeri 2 Denpasar, totaling 32 people. The data collection technique involves observation related to the implementation of actions and the achievement of results, and also presentation assessments. The data analysis technique employed includes qualitative descriptive analysis and quantitative analysis. The research results indicate an improvement in cultural arts learning outcomes in class X AK 1 from cycle I to cycle II. This can be observed through the increase in the average scores from the presentation assessments.